Mover/se(r) a gênese do corpo entre/corpos e seus trajetos no processo coreográfico - Motta, Mauricio Moraes (2014)
This paper proposes a reflection on the body between/bodies, especially in contemporary dance, in their path that starts from the choreographic construction, permeating the body of the choreographer, the dancer s body and when fulfills themselves as artistic expression, the body of the spectator. Initially discusses the body in dance as a body/space for convergence, connectedness and continuity, from the thought of the Greek philosopher Epicurus of Samos, in dialogue with the thought of Maurice Merleau-Ponty, Gilles Deleuze and José Gil. Reflect about the creation of this body/space in the relationship choreographer/dancer using as connecting thread the experiences of the author in his artistic path. Finally describes the process of creating the scenic experiment (h)áporos, which constitutes the practice scene of this dissertation, having as main objective the creation of spaces of convergence and interaction between a proponent and an affluent body that, in this move, transforms itself and the space that now cohabits / is